Analisis Peranan Otoritas Jasa Keuangan (OJK) dalam Perlindungan Nasabah Akibat Kepailitan Perusahaan Asuransi - Siregar, Indah Kurniati; Kusmilawaty, Kusmilawaty; Bi Rahmani, Nur Ahmadi (Jayapangus Press, 2025)
The Financial Services Authority (OJK) is a key government body in Indonesia that oversees the insurance sector and all other financial service providers by creating a unified regulatory and supervisory framework. The OJK has the authority to initiate insolvency actions against insurance businesses as part of its insurance sector regulation. Insuring policyholders' interests is the primary goal of these procedures. The purpose of this research is to examine how the OJK protects policyholders' rights when insurance firms declare bankruptcy. In order to provide a thorough analysis and in-depth understanding of the topic, the study employs a qualitative, descriptive-analytical methodology. The study employs secondary data, which encompasses both primary and secondary legal sources, in line with the normative legal research technique. The findings indicate that the OJK's efforts to provide legal protection for policyholders, particularly in cases of insurance claim rejections, are guided by key principles such as transparency, fair treatment, justice, confidentiality, data security, and effective complaint handling. The OJK's role in legal protection encompasses both preventive and repressive measures. Preventive actions include regulation, supervision, guidance, socialization, and complaint services, while repressive measures involve litigation, non-litigation resolution, and the imposition of administrative sanctions.